Un pied dans l’eau, un pied sur terre : trajectoires et savoirs sampaniers dans un processus de transfert de la pêche vers l’aquaculture Phù Tân (Vietnam) - Annick Thomassin (VertigO)
This article addresses the issue of the ecological knowledge transformation and resilience of semi-nomadic fishermen (Sampan people) living in the Tam Giang-Cau Hai lagoon system in Central Vietnam. Finding themselves in a context of resource depletion, massive transfer from fishing to aquaculture and incentives to settle on land, those fishermen communities are confronted to a redefinition of their relationship with the lagoon environment and resource. This case study, based on data collected during a field research related to an anthropology master’s project provides the opportunity to think about the reconstruction of the sampan peoples’ knowledge and practices through the transfer from fishing to shrimp and fish farming. This process is supervised by a team of scientists who are working to implement a community-based coastal resource management model in the area.